Company Value as Consideration in Making Individual Stock Investment Decisions (Hermeneutical-Critical Study) - Nartasari, Diah Rani (Program Doktor Ilmu Ekonomi, 2022)
Individual stock investor has many options in an investment and investment decision was influenced by so many factors, one of them is value of the firm. Value of the firm is often associated with stock price. The higher stock price means the better value of the firm. This mini-research used critic-hermeneutic research approach. Hermeneutic used for interpretation of text which told by individual stock investors in the interview. There were 8 informant interviewed in this mini-research, who had different backgrounds i.e employee, entrepreneurs, and college students. The result showed that value of the firm as useful value for investors, actually didn’t entirely used by individual stock investors, especially for investors who used technical analysis and another non-fundamental analysis in their stock analysis. Investor’s sophistication in value of the firm analysis also influenced by the other investor, so they didn’t analize it anymore. When value of the firm didn’t influence the investment decision of investor, no-effect hypothesis was applied. Whereas more sophisticated investor considered value of the firm in their investment decision. When value of the firm influenced to the investment decision of investor, mechanistic hypothesis was applied. Keywords: Individual stock investor, investment decision, value of the firm.